Identification of Interleukin-9 Producing Immune Cells in Endometrial Carcinoma and Establishment of a Prognostic Nomogram - Tong, Huan; Feng, Hao; Hu, Xiang; Wang, Meng-fei; Song, Yun-feng; Wen, Xiao-li; Li, Yi-ran; Wan, Xiao-ping (Frontiers in Immunology, 2020)
Background: Interleukin-9(IL9) plays a critical role in immunity, and the pathogenesis of endometrial cancer (EC), especially endometrioid EC (EEC), This study aimed to identify the IL9+ immune cell subsets and their pleiotropic functions and establish an optimized prognostic nomogram towards the promotion of personalized treatment of EEC. Methods: 1417 EC patients were involved in the present study. One hundred forty-three patients from tertiary gynecology centers in Shanghai between 2013 and 2019 were recruited, and the study protocol was approved by the Institutional Review Board (IRB) of Shanghai First Maternity and Infant Hospital. The genomic data of the other 1274 patients were extracted from the TCGA and the MSKCC dataset, respectively. Immune and stromal scores were calculated using the ESTIMATE R tool, and the tumor infiltration of immune cells was analyzed by using the TIMER platform. Metascape and GEPIA datasets were used for bioinformatic analysis. P< 0.05 was considered statistically significant. All statistical analyses were performed with GraphPad Prism and R studio. Results: 552 genes that were correlated with leukocyte infiltration, lymphocyte activation, and regulation of innate immune response were up-regulated in the high immune score group. More IL9+cells infiltrating was detected in high and moderate differentiated EC (p=0.04). High IL9+lymphocyte infiltration was related to a better overall survival (p=0.0027). IL9 positive cell clusters included ILC2s, Vδ2 γδT cells, mast cells, macrophages, and Th9 cells. Parameters such as FIGO stage, IL9 score, Vδ2+γδT cell infiltration, classification of differentiation, type of cancer, and diabetes mellitus were assigned a weighted number of points in the nomogram for a specific predicted 3-, 5- and 10-year OS. IL9-IL9R axis played a vital role in EEC, IL9R positive cell subgroups were also identified, and the related function was analyzed in the present study. Additionally, PR expression was relevant to a higher density of IL9+lymphocytes infiltration. However, PGRMC1 was negatively relevant to IL9R (p=4.26e-8). Conclusion: These findings indicated that IL9-IL9R axis played a vital role in EEC. The nomogram incorporating the IL9 could accurately predict individualized survival probability in EEC.